How Do Global Credit RatingAgencies Rate Firms from Developing Countries? - Li-gang Liu; Giovanni Ferri (Asian Development Bank Institute (ADBI), 2001)
What is the relative contribution of sovereign risks and firm-level credit risks in a firm'srating assignment? Or, stated otherwise, what is the information content of these components in afirm's rating? This paper intends to examine this issue, which has not been adequately addressed so far,using a tailor-made firm-level database, matching sovereign and firm ratings with firm performanceindicators reportedly used by rating agencies. The paper decomposes factors contributing to a firm'scredit rating by measuring each factor's relative weight. By matching a firm's credit risk indicatorswith its corresponding sovereign risk, we are able to disentangle the relative importance of each factorin a firm's rating assignment.We make three contributions. First, our findings reveal that sovereign risks contribute to amajor part of firms' ratings in developing countries, whereas such risks play a negligible role inassigning firms' ratings in developed countries. Second, we show that this result for developingcountries partly depends on the “country ceiling effect”—private ratings are bound upwards by theirsovereign rating—but in these countries idiosyncratic information is irrelevant even for firms whoserating would lie anyhow way below their sovereign. Accordingly, we document that the informationcontent of firm ratings is much smaller in developing countries than in developed countries. Third, weshow that cross-country indicators of information quality, rule of law and other institutional qualityindicators help explain this unsatisfactory situation but do not solve the puzzle entirely. Global ratingagencies need also to improve their rating methodology to meet the challenges of the emerging marketratings.
hdl:11540/4131
Keywords: 330